2007
DOI: 10.1007/s11373-007-9148-4
|View full text |Cite
|
Sign up to set email alerts
|

p38 MAPK in regulating cellular responses to ultraviolet radiation

Abstract: Solar ultraviolet (UV) radiation is a major environmental factor that causes DNA damage, inflammation, erythema, sunburn, immunosuppression, photoaging, gene mutations, and skin cancer. p38 mitogen activated protein kinase (MAPK) are strongly activated by UV radiation, and play important roles in regulating cellular responses to UV. In this review, we examine the role played by p38 MAPK in mediating UV-induced cell cycle, apoptosis, inflammation, and skin tanning response. We review the role played by p38 MAPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 102 publications
(104 reference statements)
7
56
0
Order By: Relevance
“…To determine whether enhanced apoptosis is a more general phenomenon of p38 inhibition, we tested 2 non-ER stress-mediated apoptotic inducers: staurosporine and UV irradiation (2). While p38 inhibition enhanced macrophage apoptosis in cells treated with staurosporine ( Figure 6F), apoptosis was suppressed in cells exposed to UV irradiation ( Figure 6G), consistent with previous reports of a proapoptotic role for p38 (34). In contrast, p38 has previously been shown to protect from pathogen-induced apoptosis (24,35,36).…”
Section: Macrophage P38α Deficiency Leads To Enhanced Macrophage Apopsupporting
confidence: 90%
See 1 more Smart Citation
“…To determine whether enhanced apoptosis is a more general phenomenon of p38 inhibition, we tested 2 non-ER stress-mediated apoptotic inducers: staurosporine and UV irradiation (2). While p38 inhibition enhanced macrophage apoptosis in cells treated with staurosporine ( Figure 6F), apoptosis was suppressed in cells exposed to UV irradiation ( Figure 6G), consistent with previous reports of a proapoptotic role for p38 (34). In contrast, p38 has previously been shown to protect from pathogen-induced apoptosis (24,35,36).…”
Section: Macrophage P38α Deficiency Leads To Enhanced Macrophage Apopsupporting
confidence: 90%
“…Several previous studies have shown that activation of p38 MAPK can have pro-or antiapoptotic effects depending on the cellular environment (2,23,24,(34)(35)(36). The important finding in the present study is that in advanced atherosclerotic plaque, p38α plays a prosurvival role in macrophages.…”
Section: Discussionsupporting
confidence: 63%
“…Finally, we observed a moderate but significant decrease in annexin V-positive staining at 72 h post-UV in SB202190-treated HDLFs (Fig. 6B), supporting a proapoptotic role for p38␣/␤ in UV-irradiated HDLFs, as previously observed in various cell lines (31). In addition, sub-G 1 peak analysis consistently revealed a slight reduction in UV-induced apoptosis in SB202190-treated cells, although this was not statistically significant (Fig.…”
Section: Effects Of Mapk Inactivation On Cell Death and Proliferationsupporting
confidence: 84%
“…Nonetheless, we can exclude some of the possible substrates. Tumor suppressor protein p53 and CCAAT/enhancer-binding protein homologous protein, for example, can be activated by p38 MAPK and activate proapoptotic factors (Ono and Han, 2000;Shi and Gaestel, 2002;Jinlian et al, 2007). However, p53 is not detectable in J774A.1 macrophages and SMCs even after stimulation with protein synthesis inhibitors (Croons et al, 2007).…”
Section: Role Of Mapk In Anisomycin-induced Macrophage Apoptosis 863mentioning
confidence: 99%